One-Person Company According to Oman Commercial Companies Law of 2019: An analytical Study - Albarashdi, Saleh Hamed; Albadi, Ali Salim (Journal of Ecohumanism, 2024)
A company, in general, undertakes economic projects that cannot be carried out by an individual trader, regardless of their abilities. The company is considered a key tool for attracting and increasing investments in various countries. Moreover, by establishing a company, individuals can benefit from the fact that these legal entities, which possess separate legal personality, allow them to control them and enter into legal relationships without being directly liable for them. In most Arab legislations regulating the provisions of commercial companies, at least two individuals are required to establish a company. However, this requirement has recently been abandoned in several countries in the region. This is what happened in Oman through the new Omani Commercial Companies Law (Law No. 18 of 2019), where it is now possible to establish a Limited Liability Company with a single person, whether a natural person or a legal entity. In this paper, the main characteristics of a single-member limited liability company will be highlighted, along with the rules concerning its management and dissolution according to the Omani Commercial Companies Law. Further, the paper will discuss the issue of the bankruptcy of a one-person company since it raises many practical challenges since the bankruptcy of the company will not lead to the bankruptcy of its owner.